Estimating ergodization time of a chaotic many-particle system from a time reversal of equilibrium noise - Tarkhov, Andrei E.; Fine, Boris V. (Arxiv, 2018)
We propose a method of estimating ergodization time of a chaotic many-particle system by monitoring equilibrium noise before and after time reversal of dynamics (Loschmidt echo). The ergodization time is defined as the characteristic time required to extract the largest Lyapunov exponent from a system's dynamics. We validate the method by numerical simulation of an array of coupled Bose-Einstein condensates in the regime describable by the discrete Gross-Pitaevskii equation. The quantity of interest for the method is a counterpart of out-of-time-order correlators (OTOCs) in the quantum regime.
Gesehen am 05.11.2020